The AbinitioD Γ A Project v1.0: Non-local correlations beyond and susceptibilities within dynamical mean-field theory - Galler, Anna; Thunström, Patrik; Kaufmann, Josef; Pickem, Matthias; Tomczak, Jan M; Held, Karsten (2017)
The ab initio extension of the dynamical vertex approximation (D $Γ$ A) method allows for realistic materials calculations that include non-local correlations beyond$GW$and dynamical mean-field theory. Here, we discuss the AbinitioD $Γ$ A algorithm, its implementation and usage in detail, and make the program package available to the scientific community.